Interstellar dust in the solar system - Sterken, Veerle Jasmin; Westphal, Andrew; Altobelli, Nicolas; Malaspina, David; Postberg, Frank (Space science reviews, 2019)
Interstellar dust from the Local Interstellar Cloud was detected unambiguously for the first time in 1992 (Grün et al. in Nature 362:428–430, 1993). Since then, great progress has been made in observing local interstellar dust in the Solar System using a variety of methods that, all together, provide complementary views of the dust particles from our local galactic neighborhood. The complementary methods discussed in this paper are: (1) in situ observations with dust detectors, (2) sample return, (3) observations of dust in the infrared, and (4) detections using spacecraft antennae. We review the current state of the art of local interstellar dust research, with a special focus on the advances made in the last ∼10 years of interstellar dust research. We introduce this paper with an overview of the definitions of interstellar dust. We describe the dynamics of the dust particles moving through the heliosphere and report on the progress made in the modelling efforts especially in the last decade. We also review the currently available in situ measurements of interstellar dust flux, speed, direction and size distribution from various missions, in specific from Ulysses and Cassini, and their interpretation in context of the dust dynamics studies. Interstellar dust composition is also reviewed from Cassini in situ time of flight measurements and from the Stardust sample return mission that both took place in the last decade. Finally, also new dust measurements from spacecraft antennae are reviewed. The paper concludes with a discussion on currently still open questions, and an outlook for the future.